Coronary Flow Reserve Assessment Via Echocardiographyin Patients with Coronary Bypass Surgery UndergoingLAD-LİMA Long Onlay-Patch Anastomosis withoutEndarterectomy - Tekin, Esra Ertürk; Uysal, Ayhan; Vezir, Özden (My University, 2021)
Objective: In severe calcified and diffuse coronary lesions, long onlay-patch anastomosis withoutendarterectomy is another technique to promote augmented blood flow especially to septalperforator branches of left anterior descending artery (LAD). In this study we aimed to demonstratethe efficacy of the long segment onlay-patch anastomosis without endarterectomy via usingcoronary flow reserve (CFR) measured by doppler echocardiography.Materiasl and Methods: Fifty six patients who underwent Coronary artery bypass grafting (CABG) onlay-patch anastomosis technique without endarterectomy were evaluated by transthoracicechocardiography for CFR which represents the rates of blood flow both during resting andmaximal hyperemia provided by dipyridamole. left anterior descending artery-left internalmammary artery (LAD-LIMA) along the long anastomosis line mid and distal flow patterns wereexamined, peak systolic and diastolic flow velocities and diastolic velocity time integral wereregistered.Results: The mean onlay-patch length was 2.97±0.72 cm. When correlation of changes incoronary flow reserve and other echocardiographic findings were evaluated, there was astatistically significant however, for all patients (normal values: CFR>2, n: 9 and low values:CFR<2, n: 6) inverse correlation between onlay-patch anastomosis length and CFR (2.97±0.72 cm;2.35±0.56 m/sec; P= 0.008, respectively). Coronary angiography was performed for the one patientwith CFR<2. Angiography showed 80% stenosis in the post anastomosis segment. Conclusion: We explained the reliability of the onlay-patch anastomosis technique withoutendarterectomy and the usability of CFR measurement with transthoracic echocardiography in thepostoperative follow-up of patients who underwent coronary bypass.
Keywords: Genel ve Dahili Tıp; Patoloji; Kalp ve Kalp Damar Sistemi; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme